Heterogeneous Photocatalytic Remediation of Phenol by Platinized Titania-Silica Mixed Oxides under Solar-Simulated Conditions - Kibombo, Harrison S.; Koodali, Ranjit T. (The Journal of Physical Chemistry, 2011)
Aperiodic mesoporous TiO2–SiO2 mixed oxide materials were platinized by the incorporation of Pt0 by three different methods to understand the role of Pt on the photocatalytic activity of phenol under solar simulated conditions. The physicochemical properties of the resultant photocatalysts were examined by powder X-ray diffractometry, nitrogen adsorption, diffuse reflectance spectroscopy, and transmission electron microscopy. These characterization techniques illustrated the enhanced morphological properties of the mesostructure such as the presence of highly crystalline anatase TiO2, large pore geometries, and active Ti–O–Si linkages, respectively. CO chemisorption analysis and TEM images accentuated the role of small Pt crystallite sizes in the development of photocatalysts with high degradation efficiencies.
Keywords: Photocatalytic; Phenol; Titania–Silica; Solar-Simulated Conditions; Oxides